Perbudakan di Ommelanden dan Wilayah Sulu Abad XVIII–XIX: Sebuah Tinjauan Komparatif - Mulyanto, Heru; Amalia, Lazzuarda Pramudita; Zaldi, Nabiel Fakriyah (Historia Madania: Jurnal Ilmu Sejarah, 2022)
The areas of Sulu and Ommelanden are discussed in this study because these two places have similarities in socio-economic elements, that is slavery which is the main focus in this study. The Dutch who held slavery in Ommelanden and the Sulu Sultan who controlled slavery in Sulu becoming an interesting topics to discuss because they raise differences in a similarity. This study aims to describe the comparison of slave management systems, slave marketing, cases that have occurred and other matters related to slavery in Southeast Asia (especially in Ommelanden & Sulu). The methodology used in this research is a historical method using international literature sources which are analyzed in depth. The results showed that slavery carried out by the Dutch in Ommelanden was more organized while slavery in Sulu was based on illegal acts and was accompanied by violence. In addition, the slaves who were rented/traded in Ommelanden were obtained legally, while the Sulu slaves were obtained through piracy and kidnapping by the Illanun & Balagingi people. The difference in the subject of management creates a fundamental difference as well. Keywords: Ommelanden, Sulu, slave market, violence against slaves, slavery laws.